Determinants of the trilemma policy combination - Hiro Ito; Masahiro Kawai (Asian Development Bank Institute (ADBI), 2014)
We present a theoretical framework for policy making based on the "impossible trinity" or the "trilemma" hypothesis. A simple optimization model shows that placing more weight in terms of preference for each of the three open macroeconomic policies - exchange rate stability, financial market openness, and monetary policy independence - contributes to a higher level of achievement in that particular policy. We then develop the first empirical framework in the literature to investigate the joint determination of the triad open macroeconomic policies based on the trilemma hypothesis. Specifically, we estimate the three policy indexes under the trilemma constraint that they must add up to a constant. By applying the seemingly unrelated regression (SUR) estimation method and employing other robustness checks, we demonstrate that simple economic and structural fundamentals determine the trilemma policy combinations. Last, we examine how deviations from the "optimal" trilemma policy combinations evolve around the time of a financial crisis. Policy combinations seem to violate the trilemma constraint when a currency, banking, or debt crisis breaks out. These findings suggest that deviations from the trilemma hypothesis would create policy stress, which would have to manifest itself in a crisis unless policy makers adjust the policy combination in a way consistent with the trilemma constraint.
Keywords: F15; F21; F31; F36; F41; O24; 330; trilemma hypothesis; macroeconomic policy; exchange rate stability; financial market openness; monetary policy independence; financial crisis; policy combination; Wirtschaftspolitik; Offene Volkswirtschaft; Wirtschaftsforschung; Makroökonomik